(untitled) (Encuentros, 2023)
The systematization of the 89 degree works of the Specialization in Environment and Local Development, of the District University, Francisco José de Caldas. These works were elaborated in the period 2010- 2018, research development during sabbatical year. The question: ¿how can higher education in the environment and local development contribute to understanding the complexity of social processes? Is the referent of the problem and the methodology based on elements of Husserl´s phenomenological reduction? The results show the weakness of the Works to inscribe the eco environmental problems in the complexity of social processes.